2017 Outbreak of Ebola Virus Disease in Northern Democratic Republic of Congo. (3rd April 2019) - Nsio, Justus; Kapetshi, Jimmy; Makiala, Sheila; Raymond, Frederic; Tshapenda, Gaston; Boucher, Nancy; Corbeil, Jacques; Okitandjate, Antoine; Mbuyi, Gisele; Kiyele, Musa; Mondonge, Vital; Kikoo, Marie Jose; et al.
Abstract: Background: In 2017, the Democratic Republic of the Congo (DRC) recorded its eighth Ebola virus disease (EVD) outbreak, approximately 3 years after the previous outbreak. Methods: Suspect cases of EVD were identified on the basis of clinical and epidemiological information. Reverse transcription–polymerase chain reaction (RT-PCR) analysis or serological testing was used to confirm Ebola virus infection in suspected cases. The causative virus was later sequenced from a RT-PCR–positive individual and assessed using phylogenetic analysis. Results: Three probable and 5 laboratory-confirmed cases of EVD were recorded between 27 March and 1 July 2017 in the DRC. Fifty percent of cases died from the infection. EVD cases were detected in 4 separate areas, resulting in > 270 contacts monitored. The complete genome of the causative agent, a variant from the Zaire ebolavirus species, denoted Ebola virus Muyembe, was obtained using next-generation sequencing. This variant is genetically closest, with 98.73% homology, to the Ebola virus Mayinga variant isolated from the first DRC outbreaks in 1976–1977. Conclusion: A single spillover event into the human population is responsible for this DRC outbreak. Human-to-human transmission resulted in limited dissemination of the causative agent, a novel Ebola virus variant closely related to the initial Mayinga variant isolated in 1976–1977 in the DRC. Abstract : In 2017, a small outbreak of Ebola virus disease occurred in the Democratic Republic of the Congo (DRC), killing half of 8 infected individuals. This outbreak was caused by a variant closely related to the Ebola virus Mayinga variant isolated from the first DRC outbreaks in 1976.